2021
DOI: 10.3389/fpls.2021.745411
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the “Green Revolution” Gene Photoperiod-1 and Its Selection Trends During Bread Wheat Breeding

Abstract: Flowering is central to the transformation of plants from vegetative growth to reproductive growth. The circadian clock system enables plants to sense the changes in the external environment and to modify the growth and development process at an appropriate time. Photoperiod-1 (Ppd-1), which is controlled by the output signal of the circadian clock, has played an important role in the wheat “Green Revolution.” In the current study, we systematically studied the relationship between Ppd-1 haplotypes and both wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…We found stage-specific expressed genes through clustering ( Figure 1C ), including known factors involved in flowering time regulation and inflorescence development. PPD1 , with Ppd-A1b/Ppd-B1a/Ppd-D1a alleles in KN9204 (Wu et al, 2021), is responsible for flowering time and expressed before the transition to flowering. (Beales et al, 2007; Boden et al, 2015; Perez-Gianmarco et al, 2020), is expressed before the transition to flowering.…”
Section: Resultsmentioning
confidence: 99%
“…We found stage-specific expressed genes through clustering ( Figure 1C ), including known factors involved in flowering time regulation and inflorescence development. PPD1 , with Ppd-A1b/Ppd-B1a/Ppd-D1a alleles in KN9204 (Wu et al, 2021), is responsible for flowering time and expressed before the transition to flowering. (Beales et al, 2007; Boden et al, 2015; Perez-Gianmarco et al, 2020), is expressed before the transition to flowering.…”
Section: Resultsmentioning
confidence: 99%
“…Variations in the Ppd-1 photoperiod genes have long been recognized as major-effect genes that control both flowering time and above-ground shoot growth (González et al 2005 ; Beales et al 2007 ; Boden et al 2015 ; Royo et al 2016 , 2018 ; Steinfort et al 2017a , b ; Ramirez et al 2018 ; Arjona et al 2018 ; Pérez-Gianmarco et al 2019 ; Zhang et al 2019 ; Wu et al 2021 ). In this study, we observed that the photoperiod insensitivity allele Ppd-D1a (PpdD1-Hap3) had the most significant impact on the nodal root-angle index, showing a remarkable 57% increase compared to considerably lower effects on other traits (e.g., − 10% for biomass, − 6% for NRN).…”
Section: Discussionmentioning
confidence: 99%